Payback - Gordon, Mary, 1949- (Pantheon Books, 2020)
"Unbeknownst to her many fans, Quin Archer, the revenge-loving queen of the reality-TV show "Payback," was once an angry teen named Heidi - and her true story may be known only to Agnes, who was her art teacher at a private New England girls' school in the 1970s. Then a young woman herself, Agnes saw a spark of originality in the brooding Heidi. But when she suggests Heidi visit the Museum of Modern Art in New York, the girl returns with a disastrous account of having been picked up at the museum by an older man. Agnes's stunned, victim-blaming response will haunt both women for decades. Gordon narrates this tale of #metoo misunderstanding, from a time before there was language to contain it, with a sharp sense of life's changing tempo, carrying us through Heidi's disappearance and reinvention as Quin, and Agnes's escape into career and family in Italy - until, inevitably, they meet again. A remarkable book about the precise weight of our words and deeds, from a writer whose moral vision is deeply rewarding in its subtlety"--Provided by publisher.